Online Course Enrollment in Community College and Degree Completion: The Tipping Point - Shea, Peter; Bidjerano, Temi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Recent research indicates that certain students are at risk of lower levels of academic performance in online settings when compared to peers who study only in the classroom.  Community college students have been a population of particular concern.  In this paper, we hypothesize that online course load and institutional quality may impact outcomes for such students at risk for lower levels of degree attainment.  Using comprehensive data from the 30 community colleges (n=45,557) of the State University of New York (SUNY), we conducted a state-wide study to examine whether there is a “tipping point” at which online course load becomes problematic for community college learners seeking to attain a degree through a mix of online and face-to-face coursework. We also test the conjecture that some institutions may excel at supporting online learner success among more at risk populations who choose online study. Results indicate that community college students who take more than 40% of their courses online begin to lose the benefits of enhanced degree completion conferred through a mix of online and face-to-face enrollment. Moderating variables are also identified and discussed.